PTU-147 Incidence and Predictive Features of Pharyngeal Pouches in a Dysphagic Population. (4th June 2013) - Murray, I A; Dalton, H R; Palmer, J; Wilde, A D; Grimes, D R
Abstract : Introduction: Pharyngeal pouches (PPs) commonly present with dysphagia. Perforation of a pouch at gastroscopy is a feared complication. Predicting patients likely to have PPs can enable selection for barium swallow to reduce this risk. PP incidence in a dysphagic population has been reported as 0.3% 1 . We investigated PP incidence and predictive demographic and clinical features in patients referred to a dysphagia hotline service over a 7 year period. 2 Methods: Analysis of prospectively collected data on demographics (age, sex) and symptoms (including duration and level of dysphagia, type [solids/liquids, progressive/intermittent], associated symptoms [weight loss, reflux, regurgitation] and outcomes of investigations of 2000 consecutive referrals for dysphagia. Logistic regression determined significant variables for predicting PPs. A consultant ENT surgeon reviewed all barium swallows of PP patients. The local ethics committee ruled the study was within the remit of audit. Results: 1775 patients were investigated through the DHL, 37 with PP (1.9% of total, 2.1% of those investigated). One of these was a re-referral, 6 years after initial pouch stapling. 20 were male (54%), mean age 80.1 years (range 58–103 years). Mean age of all patients was 68.1 years (range 17–103), 48.5% male. Two patients had PPs and oesophageal cancer. On logistic regression only age greater than 73 years and symptoms of dysphagia greater than 26 weeks were predictive of PP as final diagnosis (p < 0.001 and 0.005 respectively). Weight loss (5.4 vs 28.5%) and reflux (45.9% vs 60.6%) were less common in PP patients and regurgitation more so (62.2% vs 52.1%) but none of these were significant. Conclusion: Pharyngeal pouches in a dysphagic population are more common than previously recognised. Most though not all have pharyngeal level dysphagia. Where gastroscopy was performed as initial investigation, the procedure was likely to be incomplete although no complications occurred. Just over 50% of the PPs were thought likely to be the cause of dysphagia but less than 50% of these underwent surgery (stapling). Disclosure of Interest: None Declared References: Melleney EM, Subhani JM, Willoughby CP. Dysphagia referrals to a District General Hospital Gastroenterology unit: hard to swallow. Dysphagia 2004; 19 :78–82. doi:10.1007/s00455–003–0501–0 Murray IA, Waters C, Maskell G, Despott EJ, Palmer J, Dalton HR Improved clinical outcomes and efficacy with a nurse-led dysphagia hotline service. Frontline Gastroenterol. In press.